“Minería y empleo: caso ecuatoriano durante el periodo 1990 – 2018” - Silva Suárez, Junior Olmedo (2021)
The exploitation of natural resources represents a source of multiple economic benefits for those countries that know how to take advantage of it. According to the International Council on Mining and Metals (2021), 40% of the sector's production contributes to economies in the form of salaries and taxes. Ecuador is a country with large mining resources, therefore, the present research aimed to analyze the effect of mining activity on Ecuadorian employment during the period 1990 - 2018, to determine its short and long term relationship. The data used were taken from the United Nations University WIDER (2021), World Development Indicator of the World Bank (2021) and the KOF base of the Swiss Economic Institute (2020). Three econometric time series cointegration techniques were used to meet the objective; an autoregressive vector model, error correction model and Granger causality test. The results showed that mining production helps to reduce the unemployment rate in the long run, but no relationship was found that affirmed the same in the short run. In addition, there are other factors, such as foreign direct investment and human capital, that influence the pattern established. The policy implications point to greater state planning to articulate various sectors around mining and generate greater benefits to the territory.